Examining EFL Secondary reading Curriculum In Iraqi Kurdistan :A Review - Hamsa Hameed Ahmed; Fariza Puteh-Behak; Harison Mohd Sidek (Asian Network for Scientific Information, 2024)
At the university level in Arab world in general and in Iraq in particular, many students faced a lot of problems with their studying because of their low English proficiency, students face problems while trying to understand texts written in English. Form six is last form before university and in spite of that the students doing incessant efforts to master the English language through studying the curriculum at the sixth year in Iraq, some students still complain that they have a lot of difficulties in achieving this goal. An analysis of the EFL secondary reading curriculum in Iraqi Kurdistan (Form Six): Approaches to reading are considered as a challenge area of study. Thus, the aim of this study provides a comprehensive field survey on the various stages of the various reading approaches in EFL secondary reading curriculum. Next, the reading theories and reading strategies are given focus followed by some significant pointers to achieve effective reading. A critical review on EFL secondary reading curriculum is done at the end of the study.